Improving cardiovascular prevention in general practice: Results of a comprehensive personalized strategy in subjects at high risk. (29th August 2020) - Avanzini, Fausto; Marzona, Irene; Baviera, Marta; Barlera, Simona; Milani, Valentina; Caimi, Vittorio; Longoni, Paolo; Tombesi, Massimo; Silletta, Maria G; Tognoni, Gianni; Roncaglioni, Maria Carla; ,
Abstract: Background: Although high cardiovascular risk patients should be the main target of preventive strategies, modifiable risk factors are often inadequately controlled. Aim: To assess feasibility and results of a comprehensive personalized method for cardiovascular prevention in high risk patients followed by their general practitioner. Methods: Between 2004 and 2007, 12, 513 patients (mean age 64.0 ± 9.5 years; 61.5% males) with multiple cardiovascular risk factors or history of atherosclerotic disease were identified and followed for five years. If control of major modifiable cardiovascular risk factors (hypertension, hypercholesterolaemia, diabetes, obesity, smoking, unhealthy diet, physical inactivity) was sub-optimal, at baseline and yearly thereafter general practitioners planned with patients, with the help of a brief checklist, preventive interventions to improve the global risk profile. Main outcome was the control of the seven major modifiable cardiovascular risk factors during follow-up. Secondary outcome was the incidence of cardiovascular deaths and hospitalization for cardiovascular reasons according to the improvement in global cardiovascular risk profile during the first year. Results: Control of all major modifiable risk factors except physical inactivity improved gradually and significantly ( p  < 0.0001) during follow-up. The improvement in the global cardiovascular risk profile during the first year was independently and significantly associated with a lower rate of major cardiovascular events in the following years (hazard ratio 0.939; 95% confidence interval 0.887–0.994, p  = 0.03). Conclusions: Our comprehensive, personalized method for cardiovascular risk prevention in people at high risk appears feasible in general practice. The improvement in the global cardiovascular risk profile was associated with a better prognosis.